2019
DOI: 10.1093/ibd/izz251
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Eosinophilia Is an Independent Predictor of Vedolizumab Efficacy in Inflammatory Bowel Diseases

Abstract: Background Peripheral and mucosal eosinophilia may be associated with more aggressive disease in inflammatory bowel disease (IBD) patients. Vedolizumab blocks T lymphocytes, eosinophil adhesion, and extravasation in the gastrointestinal tract. It is not known if mucosal eosinophilia is a predictor for the therapeutic efficacy of vedolizumab. Methods This was a retrospective cohort study of IBD patients with ileal or colonic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 39 publications
3
22
1
Order By: Relevance
“…These data are in line with those of a recent study showing that distal/left-sided colitis was associated with a higher percentage of clinical remission at week 14 as compared to extensive colitis following vedolizumab treatment [14]. However, other studies failed to document an association between extent of UC and response to vedolizumab [22,23,52]. Although, it remains unclear why such studies have generated divergent results, it is conceivable that discrepancies can rely on differences in the selection of the objectives, study population, and statistical analysis adopted.…”
Section: Discussionsupporting
confidence: 90%
“…These data are in line with those of a recent study showing that distal/left-sided colitis was associated with a higher percentage of clinical remission at week 14 as compared to extensive colitis following vedolizumab treatment [14]. However, other studies failed to document an association between extent of UC and response to vedolizumab [22,23,52]. Although, it remains unclear why such studies have generated divergent results, it is conceivable that discrepancies can rely on differences in the selection of the objectives, study population, and statistical analysis adopted.…”
Section: Discussionsupporting
confidence: 90%
“…Non-responders to vedolizumab treatment had higher baseline colonic mucosal mean eosinophil counts. Whether this increased baseline eosinophil count could be used as a predictor for non-response to the humanized antibody vedolizumab should be further investigated ( 192 ). While no effects of infliximab treatment on eosinophil presence and activation status have been described, infliximab has been suggested to be effective in the early stages of fibrosis development.…”
Section: Treatment Options: Targeting Eosinophils In Ibdmentioning
confidence: 99%
“…Therefore, it is possible to use steroids for a short duration in refractory UC patients who are Th2-dominant, leading to stable maintenance treatment thereafter. Eosinophilic in ltration of the colonic mucosa has also been reported to be an indicator of resistance to treatment with vedolizumab [7] , and α4β7, the target molecule of vedolizumab, is expressed on the surface of eosinophils [29] . Therefore, one treatment strategy may be to control in ammation more e ciently by rst eliminating eosinophils in the local mucosal area by administering steroids, and simultaneously inhibiting the migration of eosinophils from blood to the mucosal in ammatory area by administering vedolizumab.…”
Section: Discussionmentioning
confidence: 99%
“…However, in recent years, it has been reported that the pathophysiology of refractory UC is associated with interleukin (IL) -33 produced by damaged colonic epithelial cells and eosinophils induced by IL-33 [4,5] . Recent studies have reported that the mucosa of intractable UC lesions has a large amount of eosinophilic in ltration [6] , and the eosinophilic in ltration of the colonic mucosa is an indicator of treatment resistance to vedolizumab [7] .…”
Section: Introductionmentioning
confidence: 99%